2014
DOI: 10.1111/1753-0407.12121
|View full text |Cite
|
Sign up to set email alerts
|

Blood glucose‐lowering effect of Tectona grandis flowers in type 2 diabetic rats: A study on identification of active constituents and mechanisms for antidiabetic action 柚木花对2型糖尿病大鼠的降糖作用:一项鉴定其活性成份与降糖作用机制的研究

Abstract: Polyphenolic active constituents present in METGF are possibly responsible for the blood glucose-lowering effect in T2D rats via an insulin-sensitizing action, as well as inhibition of α-amylase and α-glucosidase activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Recently, researchers have pursued novel natural compounds that can control blood glucose levels and effectively aid the management of diabetes without any side effects. Medicinal plants, such as Thymelaea hirsuta L., Tectona grandis flowers, Musa sapientum Linn., Asparagus officinalis L., Origanum majorana , Momordica charantia , Citrullus colocynthis , and Trigonella foenum‐graecum , are found to be better alternatives than current treatment regimens, such as sulfonylureas . The bioactive compounds present in medicinal plants are very effective in the treatment of diabetes .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, researchers have pursued novel natural compounds that can control blood glucose levels and effectively aid the management of diabetes without any side effects. Medicinal plants, such as Thymelaea hirsuta L., Tectona grandis flowers, Musa sapientum Linn., Asparagus officinalis L., Origanum majorana , Momordica charantia , Citrullus colocynthis , and Trigonella foenum‐graecum , are found to be better alternatives than current treatment regimens, such as sulfonylureas . The bioactive compounds present in medicinal plants are very effective in the treatment of diabetes .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, application of this extract to type 2 diabetic rats significantly reduced their blood glucose level. The active polyphenols present in this extract impart a blood glucose-lowering effect via insulin sensitization as well as inhibition of α-amylase and α-glucosidase activities (Ramachandran and Rajasekaran, 2014). Commercial phaseolamin, which has high α-amylase inhibitory ability, can reduce the blood glucose levels in streptozotocin-induced diabetic rats; therefore, it possesses therapeutic potential for the treatment or prevention of the complications of diabetes (De Gouveia et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This enzyme acts to inhibit glucose absorption in the small intestine. The antidiabetic activity of PM through inhibition of α-glucosidase was also concluded by Elya et al (5) The fruit of PM is thought to contain flavonoids that can increase insulin secretion, alter the metabolism of Ca 2+ (25) and regenerate the pancreatic islets of Langerhans, particularly the β-cells. (26) Similar findings were obtained in the study that was conducted by Arjadi and Mustafa (27) who concluded that PME can decrease the blood glucose level in diabetic rats, and regenerate the cells of the pancreatic islets of Langerhans of diabetic rats.…”
Section: Discussionmentioning
confidence: 69%